Reading dream literature and the Big Five personality factors - Schredl, Michael; Göritz, Anja (Dreaming, 2020)
Books on dreams and dream interpretation have a very long history and still enjoy a wide readership. However, empirical studies regarding this topic are scarce. The present online study (N = 2,492) elicited frequency of reading dream literature and self-rated benefit of this reading. The findings indicate that reading something about dreams is quite common in the general population, and persons can benefit from this dream literature regarding the understanding of their own dreams. Positive Attitude Toward Dreams, Gender, Education, and Openness to Experience were some of the factors related to reading dream literature, whereas the self-rated benefit was related to the Amount of Material Read and Attitude Toward Dreams. Pursuing this line of research might help to identify approaches to dreams that are effective and might be applied in the context of psychotherapy. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Gesehen am 09.05.2022